(untitled) (Journal of the College of Basic Education, 2022)
The concept of civilization is one of the concepts that attracted the attention of researchers and thinkers because of its meanings, connotations and values ​​that varied according to different intellectual visions and data. Civilization may sometimes refer to culture according to the views of some writers who see it as combining creative and intellectual achievements, despite the consensus Some writings indicate that the concept of culture is something different from civilization, being more general and comprehensive than civilization.And at a second time, it refers to civilization and progress because of the methods and capabilities that support the people and their renaissance.This image, in which the concepts of civilization, progress, and culture overlap, is related to the modern intellectual perception, as it was derived from it after (the concepts) had undergone some intellectual modifications and formulations.